KONSEP DIRI IBU DAN REMAJA PADA KELUARGA CERAI DAN UTUH - Sukaidawati, Lisnani; Krisnatuti, Diah; Megawangi, Ratna (Jurnal Ilmu Keluarga dan Konsumen, 2016)
This study aimed to analyze the influence of family characteristics, characteristics of teenager, and self-concept of mother on self-concept of teenager in divorce and intact family. Population of this study was teenager with aged 12-14 years old who lived with their mother. Samples were taken from three secondary schools in the District of West Bogor and three junior high schools in the District of Tanah Sareal, Bogor City. Sampling of teenagers from divorce families was using purposive sampling technique. Collected and qualified samples were 79 students from all students of class VII and VIII. Meanwhile, sampling of teenager from intact families was using random sampling techniques based on a list of names of students and classes that exist in each school. The number of samples required is equal to the amount of sample collected on teenager of divorce family as many as 79 students, so this study involving 158 teenager students and 158 mothers of teenager students. The results indicate that the adolescent self-concept was significantly influenced by mother self-concept on the spiritual dimension, honesty, academic, emotional stability, and physical appearance. Meanwhile, the teen age, marital status, mother's age, mother's occupation, and family income has no effect on adolescent self-concept.